2005-06 Spring Timetable - Division of Enrollment Management, Office of the Registrar (UW Madison, 2005)
Official copy of the Spring 2005-06 Timetable, created on 11/2/05.
This e-records series consists of the Timetable which contains a list of authorized courses and course numbers, meeting and exam schedules, number of credits, prerequisites, and instructors. This Timetable record is a snapshot taken from the ISIS database the third week of classes each semester
Keywords: Timetable; Course Listing